Medication safety in pediatric anesthesia: An educational review and a call to action. Issue 1 (28th October 2022) - Jones‐Oguh, Sheri; Elliott, Elizabeth M.; McClung Pasqualino, Heather; Harris, Kathleen; Isserman, Rebecca S.
Abstract: Children presenting for anesthesia are at high risk for medication error during their care. In this educational review, we address the rates of medication error in pediatric patients undergoing anesthesia, why they are at higher risk than adults, and why reporting chronically underestimates the number of medication errors incurred during the anesthetic care of children. We also introduce the Anesthesia Patient Safety Foundation and Wake Up Safe, two safety organizations that have led the call to decrease medication errors. We discuss various tools to increase medication safety, as championed by Anesthesia Patient Safety Foundation and Wake Up Safe, including human factors research and highlight a few studies that have evaluated and addressed medication safety in the anesthesia environment.